The effect of the 8.2 ka cold event on Fennoscandian hunter-gatherer metapopulation inferred from climatic, environmental, and archaeological signals - Mikael A. Manninen; Roope O. Kaaronen; Jussi T. Eronen; Miikka Tallavaara (Quaternary Environments and Humans)
The effects of the 8.2 ka cold event in the Fennoscandian Peninsula have been discussed in palaeoclimatological and archaeological studies for more than two decades. Here we present the first overview of human responses to the abrupt 1–3 °C cooling in Fennoscandia. We summarize the results of 27 archaeological studies discussing the effects of the event on Fennoscandian foragers alongside with a survey of climatic and environmental proxy records that show changes during the event in the whole region. We argue that since forager populations, particularly in heterogenous environments like those found at the higher latitudes, were vulnerable to multi-decennial climatic downturns, they probably utilized a variety of strategies known from the archaeological and ethnographic record to mitigate unpredictable environmental variability. We further suggest that the archaeological cases indicate that such strategies were in use and that the use of these strategies, especially when put into effect simultaneously, affected foragers also in areas where the effects of the climate event were less severe. We therefore suggest that the effect of the cold event was felt throughout the forager network and that a model of metapopulation response to the 8.2 ka cold event in Fennoscandia can be presented. The model needs to be further developed and tested in future work.